Penerapan Metode Djikstra Pencarian Rute Terpendek Sekolah Luar Biasa (SLB) di Kota Medan - Anisa Pitri (STMIK Budi Darma, 2018)
Medan City is one of the regions that has diverse and quality educational potential. With the potential that exists, all efforts have been made by the provincial government, especially the Medan City Office to promote and advance the world of education, especially education in Special Schools. Therefore a geographic information system is needed which produces the most effective information on road guidance to get to the destination of these activities. One method that can be used in finding the shortest route is Dijkstra's algorithm. Dijkstra's algorithm finds the shortest route from a specific node to another specific node and if it continues it will give the shortest route from the specific node to all other vertices in a graph. Making GIS to find out the location of web-based Extraordinary Schools can help or as an alternative technology in the development of the world of education itself. At present the web is one source of information that is widely used for promotional facilities for schools in an area. Through GIS technology, it is necessary to develop an application that is able to provide road information for Medan City which can show the shortest route to the special school in Medan.